2004
DOI: 10.1212/01.wnl.0000098936.46730.64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epilepsy and antiepileptic drugs on male reproductive health

Abstract: CBZ, OXC, and VPA are associated with sperm abnormalities in men with epilepsy. In addition, VPA-treated men with generalized epilepsy who have abnormal sperm may have reduced testicular volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
0
19

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 25 publications
10
120
0
19
Order By: Relevance
“…Particularly, VPA causes adverse effects of male reproductive parameter in human and animals. Previous studies have shown that the testosterone levels and semen qualities of epileptic men being treated with VPA significantly decreased (Herzog, 2008;Bauer et al, 2004;Isojärvi et al, 2004;Roste et al 2003). Bauer et al have suggested that such adverse effects involved male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, VPA causes adverse effects of male reproductive parameter in human and animals. Previous studies have shown that the testosterone levels and semen qualities of epileptic men being treated with VPA significantly decreased (Herzog, 2008;Bauer et al, 2004;Isojärvi et al, 2004;Roste et al 2003). Bauer et al have suggested that such adverse effects involved male infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, VPA affects male reproductive system in both men and experimental animals. In the epileptic men treated with VPA, their testosterone levels and semen qualities have been significantly decreased (Herzog, 2008;Bauer et al, 2004;Isojärvi et al, 2004;Sveberg Roste et al, 2002) involving infertility (Bauer et al). In animals, VPA significantly decreases FSH, LH, and testosterone hormones with testicular damages (Khan et al, 2011;Krogenase et al, 2008;Hamza & Amin, 2007;Svenberg Roste et al;Nishimura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Other common forms of reproductive dysfunctions in women with epilepsy include: hypothalamic amenorrhea with low gonadotropin and estrogen levels and diminished luteinizing hormone (LH) response to the gonadotropin-releasing hormone (GnRH) (Herzog et al, 1986), poly-or oligo-menorrhea, hirsutism, functional hyperprolactinemia with galactorrhea, sub-or infertility and premature menopause (Bauer & Cooper-Mahkorn, 2008). Decreased libido, abnormal semen analysis with reduced sperm count, abnormal sperm morphology and impaired motility and reduced fertility have also been overrepresented in males with epilepsy (Isojarvi et al, 2004). Antiepileptic drugs, as well as seizures, seem to contribute to these sexual and reproductive dysfunctions.…”
Section: Hypothalamus-pituitary-gonads Axismentioning
confidence: 99%
“…These alterations are likely related to a liver enzyme induction, which leads to an increase of the sex hormone-binding globulin and a reduction of the bioavailability of serum-free sex hormone levels in both genders (Opaleke & Helmers, 2007). In contrast, testosterone and androgens are elevated in association with valproate treatments (Herzog et al, 2006;Isojarvi et al, 2004). Clinical data on gonads dysfunctions led to investigate the role of sex hormones on epilepsy mechanisms.…”
Section: Hypothalamus-pituitary-gonads Axismentioning
confidence: 99%